The Impact of Recession on the Distribution of Annual Unemployment - Beach, Charles; Kaliski, S.F. (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l'Université Laval, 1986)
The authors use microdata from the Canadian Annual Work Patterns Survey for 1978, 1980 and 1982 to compare the distributions of the annual unemployment experiences of persons.